"Nano‐Pearl‐String" TiNb2O7 as Anodes for Rechargeable Lithium Batteries. Issue 1 (27th August 2012) - Tang, Kun; Mu, Xiaoke; van Aken, Peter A.; Yu, Yan; Maier, Joachim
<x xml:space="preserve">Abstract</x> "Nano‐Pearl‐String" TiNb2O7 is fabricated by a simple and facile electrospinning method. Used as anode material for lithium‐based batteries, this novel nano‐structured material exhibits superior performance, i.e., high rate capability combined with good capacity retention upon cycling. Thus, the electrospun TiNb2O7 nanofibers are promising as an anode material for high power lithium batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>